Gas tonometry for evaluation of gastrointestinal mucosal perfusion: experimental models of trauma, shock and complex surgical maneuvers - Part 1 - Figueiredo,Luiz Francisco Poli de (2002)
Substantial clinical and animal evidences indicate that the mesenteric circulatory bed, particularly the gut mucosa, is highly vulnerable to reductions in oxygen supply and prone to early injury in the course of hemodynamic changes induced by trauma, shock, sepsis and several complex surgical maneuvers. Gut hypoxia or ischemia is one possible contributing factor to gastrointestinal tract barrier dysfunction that may be associated with the development of systemic inflammatory response and multiple organ dysfunction syndrome, a common cause of death after trauma, sepsis or major surgeries. Monitoring gut perfusion during experiments may provide valuable insights over new interventions and therapies highly needed to reduce trauma and sepsis-related morbidity and mortality. We present our experience with gas tonometry as a monitor of the adequacy of gastrointestinal mucosal perfusion in clinical and experimental models of trauma, shock and surgical maneuvers associated with abrupt hemodynamic changes, such as aortic occlusion and hepatic vascular exclusion. Next issue we will be presenting our experience with gas tonometry in experimental and clinical sepsis.